TALENT MANAGEMENT ASSESSMENT & IMPROVEMENT IN GOPLAY: A DIGITAL START-UP COMPANY - Putra, M Shahriza Rijaldi; Habyeldy, Boy; Yahya, Ignatius Ronny; Hollis, Merny; Indrajaya, Amelia Naim (Sekolah Tinggi Manajemen IPMI, 2024)
This report assesses the talent management system of XYZLive, a tech startup in Indonesia specializing in video-on-demand and livestream services. The company faces challenges in recruitment, talent retention, and organizational development. Through a comprehensive methodology involving questionnaires, interviews, and direct observation, key issues were identified in inflow, throughflow, and outflow talent management processes. Solutions proposed include defining core competencies, establishing a talent pool, nurturing a coaching culture, and implementing a structured training and development pipeline. The implementation of these strategies aims to enhance recruitment efficiency, reduce employee turnover, and ensure continuous employee growth. Ultimately, the report offers actionable solutions to improve XYZLive's talent management system, fostering sustainable organizational growth and employee satisfaction.